Ubiquitin/proteasome-rich particulate cytoplasmic structures (PaCSs) in the platelets and megakaryocytes of ANKRD26-related thrombocytopenia - Necchi, Vittorio; Balduini, Alessandra; Noris, Patrizia; Barozzi, Serena; Sommi, Patrizia; di Buduo, Christian; Balduini, Carlo L.; Solcia, Enrico; Pecci, Alessandro (Thrombosis and Haemostasis, 2013)
ANKRD26-related thrombocytopenia (ANKRD26-RT) is an autosomaldominant thrombocytopenia caused by mutations in the 5’UTR of the ANKRD26 gene. ANKRD26-RT is characterised by dysmegakaryopoiesis and an increased risk of leukaemia. PaCSs are novel particulate cytoplasmic structures with selective immunoreactivity for polyubiquitinated proteins and proteasome that have been detected in a number of solid cancers, in the epithelia of Helicobacter pylori gastritis and related preneoplastic lesions, and in the neutrophils of Schwachman- Diamond syndrome, a genetic disease with neutropenia and increased leukaemia risk. We searched for PaCSs in blood cells from 14 consecutive patients with ANKRD26-RT. Electron microscopy combined with immunogold staining for polyubiquitinated proteins, 20S and 19S proteasome showed PaCSs in most ANKRD26-RT platelets, as in a restricted minority of platelets from healthy controls and from subjects with other inherited or immune thrombocytopenias. In ANKRD26-RT platelets, the PaCS amount exceeded that of control platelets by a factor of 5 (p<0.0001). Immunoblotting showed that the higher PaCS number was associated with increased amounts of polyubiquitinated proteins and proteasome in ANKRD26-RT platelets. PaCSs were also extensively represented in ANKRD26-RT megakaryocytes, but not in healthy control megakaryocytes, and were absent in other ANKRD26-RT and control blood cells. Therefore, large amounts of PaCSs are a characteristic feature of ANKRD26-RT platelets and megakaryocytes, although these novel cell components are also present in a small subpopulation of normal platelets. The widespread presence of PaCSs in inherited diseases with increased leukaemia risk, as well as in solid neoplasms and their preneoplastic lesions, suggests a link of these structures with oncogenesis.
Keywords: ANKRD26-related thrombocytopenia; inherited thrombocytopenia; ubiquitin/proteasome system; dysmegakaryopoiesis